Analysis of Job Satisfaction Antecedents and its Impact on Hospital Performance from The Perspective of Healthcare Professionals at XYZ Hospital in East Java - El Hamzah, Salsabilla Maula Zalfa; Meilani, Yohana Cahya F. Palupi (Syntax Literate, 2024)
Company performance is an important component in a wide range of empirical research, particularly business policy research. The performance of the company is essentially a complex phenomenon with multiple dimensions and known to be correlated with job satisfaction among healthcare professionals. Therefore, understanding the factors associated with job satisfaction is important. The purpose of this study was to analyze the antecedents of job satisfaction and analyze their impact on hospital performance from the perspective of healthcare professionals. This research was conducted at XYZ Hospital. This research method is a quantitative study with a total sample of 160 healthcare professionals respondents who meet the research criteria. The research sample was taken using a purposive sampling method and data collection was carried out by distributing questionnaires online. The data obtained were analyzed using SmartPLS. The results of this study indicate that there are five independent variables as antecedents of job satisfaction. These variables are social support, work operation requirements, healthcare professional-patient relationship, work-family conflict, and working conditions. In social support variables, work operation requirements, healthcare professional-patient relationship, and working conditions have a positive effect on job satisfaction and have a significant effect while the work-family conflict variable also has a significant impact but has a negative effect on job satisfaction (T-statistic>1.645 and P-value <0.05). In addition, job satisfaction also significantly-positively affects hospital performance (T-statistic>1.645 and P-value <0.05). Furthermore, job satisfaction is significant (T-statistic>1.645 and P-value <0.05) mediates social support, healthcare professional-patient relationship, work-family conflict, and working conditions on hospital performance.